A Novel Production Method for Nitridosilicate‐type Phosphors1. Issue 12 (9th August 2013) - Cakmak, Hasan; Jansen, Martin
Abstract M 2–xEuxSi5N8 (M = Ca, Sr, and Eu), well performing orange‐to‐red phosphors for white‐LED applications, were prepared with a novel production route based on employing molecular and polymeric precursors. The procedure presented allows a one‐pot, solution‐based synthesis of the desired phosphors by reacting SiCl4 with liquid NH3, in which Ca, Sr, and Eu metals are dissolved, or Eu[N(Si(CH3)3)2]3 is suspended. The significant advantages of this new approach over the conventional solid state syntheses are easily achievable high purities of the starting compounds, and thus of the final phosphors, as well as processing at mild conditions, avoiding laborious handling and complex equipments.